Oud neg.nr. 731243-731248. 'Overdracht sleutel woningen Soest, Stichting Eigen Woningbezit' - Haas, Joh. de,
Oud neg.nr. 731243-731248. 'Overdracht sleutel woningen Soest, Stichting Eigen Woningbezit'.